USE OF THE GREGORIAN CHANT IN HEALTH: A NARRATIVE BIBLIOGRAPHICAL REVIEW - Ana Paula Almeida; Maria Julia Paes da Silva (Universidade Federal do Paraná, 2012)
The objective of this study was to review the scientific literature with a view to identifying the publications about the Gregorian chant in the area of health. It is a bibliographical narrative review study with a quantitative approach. The data was collected in the period January - April 2011, without time or language limits. In total there were 149 articles of which 128 were analyzed in full, as 21 articles were not located. In this analysis, no article met the inclusion criteria, that is, the Gregorian chant was not cited as music for intervention in healthcare. Considering that the Gregorian chant is an innovative issue in healthcare, it is necessary to undertake a review of the descriptors and carry out research to refine its potential.